The Implementation of Contrastive Analysis Based Arabic Learning - Raswan, Raswan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
As well as other learning process, the successful Arabic learning can be achieved through several steps. This study aims to explain those steps, and it uses library research. Method of this study covers finding data and sources related to the contrastive analysis in Arabic learning; analyzing the data as well as the sources; and drawing conclusion. The approach used in the learning process can be categorized as a learning difficult foreign language, if it is considered as the perspective in understanding the material. The difficult language is particularly the one that has different systems/subsystems with mother tongue. On the other hand, if the approach is considered as a belief, the successful key to achieve is the use of contrastive analysis. We have to work hard to overcome students' learning difficulties by doing contrastive approach and analysis firstly. However, the most significant part is the goal using contrastive analysis. As the result of this study, hopefully learning Arabic occurs progressively, and absolutely the teaching materials and learning steps need teachers’ ability in mastering the contrasted languages. That is the main factor in achieving the learning to be developed further in using this approach.